A 'fertile ground for poisonous doctrines'? Understanding far-right electoral appeal in the south Pennine textile belt, c.1967-1979. Issue 2 (2nd April 2020) - Collinson, Marc
ABSTRACT: Historical far-right organisations have long proved pervasive, but are rarely interpreted as competitive political parties. While these minority parties and movements never secured significant representation, they influenced municipal and constituency political activity. Focusing on the 'textile belt' of Eastern Lancashire and West Yorkshire, this article seeks to understand how far-right organisations engaged in local electoral politics. It considers the influence of regional economic changes, caused by industrial realignment, and how opponents, primarily local Labour parties, interpreted post-war fascism and the concerns it engendered. The article then examines the growing influence of Labour's anti-fascist campaigns, the popular appeal of far-right politics, and the composition of such group's memberships. As far-right institutional archives are limited, the article uses material produced by predominant local Labour parties. Alongside providing new perspectives, it encourages scholars to interpret far-right organisations as electoral actors, rather than mere cultural and political pariahs.